2017
DOI: 10.1007/s12325-017-0639-z
|View full text |Cite
|
Sign up to set email alerts
|

Predictors for the Treatment Effect of Sodium Glucose Co-transporter 2 Inhibitors in Patients with Type 2 Diabetes Mellitus

Abstract: We show that type 2 diabetes patients who received the greatest glucose-lowering effect with SGLT2 inhibitor treatment were those with preserved renal function (high baseline eGFR) and high baseline HbA1c levels. Moreover, SGLT2 inhibitor treatment efficacy could be predicted by the patients' initial response to treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
12
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 20 publications
6
12
1
Order By: Relevance
“…The decreased HbA1c levels were associated with improvement in the liver function. Consistent with previous studies [10] , [11] , [12] , SGLT2 inhibitors decreased the HbA1c levels regardless of the baseline BMI. Moreover, we propose the novel use of 1,5-AG in predicting the hypoglycemic effect of SGLT2 inhibitors.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The decreased HbA1c levels were associated with improvement in the liver function. Consistent with previous studies [10] , [11] , [12] , SGLT2 inhibitors decreased the HbA1c levels regardless of the baseline BMI. Moreover, we propose the novel use of 1,5-AG in predicting the hypoglycemic effect of SGLT2 inhibitors.…”
Section: Discussionsupporting
confidence: 91%
“…1,5-AG remained the most beneficial factor after the multivariate analysis. 1,5-AG has detective ability more useful for patients than HbA1c value or eGFR value, which was previously reported [12] .…”
Section: Discussionmentioning
confidence: 56%
“…Considering these results, an SGLT2i was frequently added to the regimens of obese patients in our study. Additionally, it has been reported that the efficacy of SGLT2is is greater in patients with preserved renal function than in those without preserved renal function [22,23]. In our study, the SGLT2i add-on group demonstrated higher eGFR than the other two groups.…”
Section: Discussionsupporting
confidence: 54%
“…Previous RCTs have reported that the decreases of HbA1c were −0.50% to 0.80% from a baseline of 7.90% to 9.20% after the administration of DAPA [1415161718]. The effect of DAPA was affected by baseline HbA1c level and eGFR [19]. Our patients' baseline HbA1c level was not higher than that of previous trials.…”
Section: Discussioncontrasting
confidence: 56%